1996
DOI: 10.1002/chin.199621165
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Bz1 Receptor Subtype Specific Ligands. Synthesis and Biological Properties of βCCt, a Bz1 Receptor Subtype Specific Antagonist.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Thus, the nonspecific effects of 3-PBC on sucrose drinking in previous studies at high doses may be due to action at α2/3/5GABA A receptors. However, the results reported in the present study agree with the reported selectivity data for both compounds (Yin et al, 2010, Cox et al, 1995). Importantly, we did not observe any signs of ataxia following 3-PBC or βCCT administration at the doses that increased latency in alcohol drinkers in the present study, suggesting that the observed effects are not due to nonspecific muscle-relaxant or motor-sedative effects (Tan et al, 2011, Licata et al, 2005, Rowlett et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the nonspecific effects of 3-PBC on sucrose drinking in previous studies at high doses may be due to action at α2/3/5GABA A receptors. However, the results reported in the present study agree with the reported selectivity data for both compounds (Yin et al, 2010, Cox et al, 1995). Importantly, we did not observe any signs of ataxia following 3-PBC or βCCT administration at the doses that increased latency in alcohol drinkers in the present study, suggesting that the observed effects are not due to nonspecific muscle-relaxant or motor-sedative effects (Tan et al, 2011, Licata et al, 2005, Rowlett et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…The short-acting, nonselective benzodiazepine agonist triazolam (Huang et al, 2000, Ziegler et al, 1983), and the α1GABA A -preferring agonist zolpidem (Crestani et al, 2000) were obtained from Sigma/RBI., St. Louis, MO. The nonselective benzodiazepine antagonist flumazenil (Hunkeler et al, 1981), α1GABA A -preferring antagonist b-carboline-3-carboxylate-tert-butyl ester (βCCT)(Yin et al, 2010, Cox et al, 1995), and nonselective benzodiazepine inverse agonist ethyl β-carboline carboxylate (βCCE)(Cowen et al, 1981) were either purchased from Sigma/RBI or provided by Dr. Jim Cook. The α1GABA A -preferring antagonist 3-propoxy-β-carboline hydrochloride (3-PBC) was provided by Dr. Cook (Yin et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, diazepam- and zolpidem-induced ataxia on the rotarod in rats were successfully antagonized with the α 1 -selective antagonist ßCCt. Because of its 20-fold selectivity for α 1 -GABA A receptors compared with α 2 -GABA A and α 3 -GABA A receptors, ßCCt is one of the most selective BZ-site ligands identified to date (Cox et al 1995; Huang et al 2000). In many behavioral studies, ßCCt successfully reversed effects of BZs related to the α 1 -GABA A receptor subtype, such as ataxia, sedation and anticonvulsant activity (Griebel et al 1999; Platt et al 2002; Savić et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Different effects of allosteric positive modulators of GABA A receptors may be explained by targeting different subunits of the GABA A receptor complex. The α1 subunit protein and its role in aggressive behavior was investigated pharmacologically due to the availability of α1-preferring agonists, such as zolpidem and antagonists such as β-CCt and 3-PBC (Cox et al 1995; Huang et al 2000). The α1 subunit appears relevant in the aggression-heightening effects of midazolam and alcohol, since these effects can be attenuated by the alpha1 subunit-preferring antagonists (de Almeida et al 2004; Gourley et al 2005).…”
Section: Discussionmentioning
confidence: 99%